2022
DOI: 10.1002/ar.25137
|View full text |Cite
|
Sign up to set email alerts
|

Curcumenol improves renal function in 5/6 nephrectomy‐induced chronic renal failure rats via the SIRT1/NF‐κB pathway

Abstract: The present work aimed to explore the protective effects of curcumenol and evaluate its pharmacological mechanisms in 5/6 nephrectomy‐induced chronic renal failure (CRF). Rats with CRF were administrated curcumenol and the effects on renal functions were investigated. Renal function examinations were carried out, whereas serum levels of inflammatory mediators, including NF‐κB, MCP‐1 and IL‐1β were analyzed by ELISA. The mRNA expression levels of SIRT1, p65 and IκBα were measured by qRT‐PCR, and the SIRT1 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Previous research has also shown that Ginsenoside Rb1 and Salvianolic Acid D not only protect against renal fibrosis but are also linked to the restoration of mitochondrial function [32][33][34]. Additionally, Dimethylcurcumin and curcumenol have demonstrated efficacy in treating renal disorders [35,36]. Furthermore, chemicals such as 2-hydroxy-3-phenylpropanoic acid and tanshinone I have been proven to be effective antioxidants [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also shown that Ginsenoside Rb1 and Salvianolic Acid D not only protect against renal fibrosis but are also linked to the restoration of mitochondrial function [32][33][34]. Additionally, Dimethylcurcumin and curcumenol have demonstrated efficacy in treating renal disorders [35,36]. Furthermore, chemicals such as 2-hydroxy-3-phenylpropanoic acid and tanshinone I have been proven to be effective antioxidants [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…After increasing the mitochondria mass and function in myotubes, it was reported to promote the initiation of myogenesis and the formation of functional myotubes. Guanghui Zhong found that curcumenol could improve renal function in 5/6 nephrectomy rats with chronic renal failure [162].…”
Section: Other Effectsmentioning
confidence: 99%
“…Although this study confirmed the activity of TFA, the related specific molecular mechanisms and signaling pathways need to be further identified. In addition, in another study, Zhong et al (2023) found that curcumenol could improve renal function in 5/6 nephrectomy‐induced chronic renal failure rats via the SIRT1/NF‐κB pathway. To be sure, these studies both emphasized the importance of exploring new therapies for diabetes nephropathy from the TCM perspective.…”
Section: Introductionmentioning
confidence: 98%